Understanding the charge transfer dynamics in 3D-1D nanocomposites over solar driven synergistic selective valorization of lignocellulosic biomass: a new sustainable approach - Jaryal A.; Singh A.K.; Dhingra S.; Bhatt H.; Sachdeva M.; Ghosh H.N.; Indra A.; Kailasam K. (My University, 2025)
Photocatalytic redox valorization of lignocellulosic biomass to fine chemicals is in its infancy stages where it can be effectively utilized for sustainable energy conversion. In this direction, an effective 3D-1D (Aeroxide P25 TiO2 and CdS) nanocomposite has been demonstrated to upgrade several biomass-derived platform chemicals (e.g. HMF, FFaL, vanillyl alcohol) in a selective and synergistic redox pathway under visible light irradiation for the first time. The successful utilization of the photocatalytic system resulted in the visible light-driven selective hydrogenation of HMF to BHMF along with the coproduction of H2 without the addition of any reducing agent under natural sunlight. In addition, the simultaneous production of valuable commodity chemical, i.e. vanillin, through oxidation has also been earmarked. The intimate interfacial contact between CdS as a visible light active photocatalyst and P25 TiO2 as an active hydrogenation site assists the facile migration of photogenerated electrons towards P25 TiO2. The coupling of electrons with in situ generated protons led to 95% yield of BHMF whereas oxidative photogenerated holes yielded 35% vanillin, thus abolishing the need for extra redox additives. The synergistic effect bestowed by the semiconductor heterojunction manifested excellent photoredox activity accompanying strong inter-particle interactions which were thoroughly investigated by employing electrochemical, PL, XPS and transient absorption spectroscopy (TAS). Thus, a new sustainable “biomass-based photo-refinery” and cost-effective low carbon-intensity approach has been elucidated for visible light-based hydrogenation activity of TiO2 unveiling a fabrication strategy of photocatalysts with efficient solar spectrum harvesting. © 2024 RSC.